Multifunctional PEGylated Niosomal Nanoparticle-Loaded Herbal Drugs as a Novel Nano-Radiosensitizer and Stimuli-Sensitive Nanocarrier for Synergistic Cancer Therapy - Afereydoon, Saeid; Haghiralsadat, Fateme; Hamzian, Nima; Shams, Ali; Hemati, Mahdie; Naghib, Seyed Morteza; Shabani, Masoud; Zandieh-doulabi, Behrouz; Tofighi, Davood (Frontiers in Bioengineering and Biotechnology, 2022)
Today, the efficient treatment for breast cancer is Radiotherapy (R.T.). To overcome the radioresistant property of cancer cells, radiosensitizing agents can be used in combined irradiation as a special place. By accumulating the cells in the G2 phase, curcumin can enhance the radiosensitive phenomenon of cancer cells and decrease cancer cell survival. The encapsulation of curcumin in a niosomal delivery system enhances aqueous solubility and bioavailability, which results in higher radiosensitive activity. This paper studies the enhancement of the radiosensitizing effect of curcumin-loaded nanoniosome when combined with irradiation. We developed PEGylated nanoniosome formulations based on tween 60, cholesterol, DOTAP, and DSPE-PEG (at 70:30:10:5) with 0.5 mg.ml-1 curcumin by thin-film hydration method. Then, we assessed at the point of -, particle size and zeta potential, entrapment efficiency, and drug release. For the cytotoxicity and apoptosis experiments, different doses of irradiation and different concentrations of free curcumin and curcumin-nanoniosome (single or combined treatment with irradiation) were examined on breast cancer cells. The particle size and zeta potential of curcumin-nanoniosome were 117.5 nm and -15.1 mV, respectively. Entrapment efficiency (EE%) and loading capacities were 72.3% and 6.68%, respectively. The drug release during 6 h was 65.9%. Cell survival in the presence of curcumin at the doses of 1 and 3 Gy showed a significant reduction compared to the irradiation at 48 and 72 h(P≤0,000), and also curcumin-containing nanoniosomes significantly increased cytotoxicity and apoptosis with synergistic effect with a combination of irradiation in comparison with free curcumin. The findings indicate that the efficacy of pretreatment with the curcumin-nanoniosome as a radiosensitizer during Radiotherapy enhance irradiation-induced breast cancer cell apoptosis and is a propitious tactic for more effective breast cancer therapy.